Coaching Transition and Nature of Change: An Examination of NCAA DI Team Sports - Johnson, James; Elam, Nick; Matz, Davis (Journal of Intercollegiate Sport, 2024)
NCAA Division I team sport head coaches typically end their coaching roles by taking a more prestigious and lucrative position, or by being fired. These differences in the nature of the leadership change suggest differences in programmatic conditions at the time of change. How a leader leaves the program undoubtedly reverberates through the program resulting in coaches, players, administrators, and fans with varying levels of satisfaction. While literature is replete with the impact of leadership changes, there is little evidence to distinguish among nature of change, and strong evidence that a negative head coaching change precedes athletic and academic decline. Thus, this study investigated 414 NCAA Division I team–sport head coaching changes using a variety of athletic and academic variables to determine what best predicts specific types of coaching changes. Results indicated athletic success has the strongest relationship and is most predictive, as expected, particularly in revenue sports. Other noteworthy findings, however, revealed female coaches have less negative coaching changes than males, and that hiring an alum or having a high Academic Progress Rate predicted a negative change. These findings reveal there are variables beyond winning that influence the nature of change and establish patterns that could assist administrators in times of transition.